Antidepressant-induced ubiquitination and degradation of the cardiac potassium channel hERG - Dennis, Adrienne T.; Nassal, Drew; Deschenes, Isabelle; Thomas, Dierk; Ficker, Eckhard (The journal of biological chemistry, 2011)
The most common cause for adverse cardiac events by antidepressants is acquired long QT syndrome (acLQTS), which produces electrocardiographic abnormalities that have been associated with syncope, torsade de pointes arrhythmias, and sudden cardiac death. acLQTS is often caused by direct block of the cardiac potassium current IKr/hERG, which is crucial for terminal repolarization in human heart. Importantly, desipramine belongs to a group of tricyclic antidepressant compounds that can simultaneously block hERG and inhibit its surface expression. Although up to 40% of all hERG blockers exert combined hERG block and trafficking inhibition, few of these compounds have been fully characterized at the cellular level. Here, we have studied in detail how desipramine inhibits hERG surface expression. We find a previously unrecognized combination of two entirely different mechanisms; desipramine increases hERG endocytosis and degradation as a consequence of drug-induced channel ubiquitination and simultaneously inhibits hERG forward trafficking from the endoplasmic reticulum. This unique combination of cellular effects in conjunction with acute channel block may explain why tricyclic antidepressants as a compound class are notorious for their association with arrhythmias and sudden cardiac death. Taken together, we describe the first example of drug-induced channel ubiquitination and degradation. Our data are directly relevant to the cardiac safety of not only tricyclic antidepressants but also other therapeutic compounds that exert multiple effects on hERG, as hERG trafficking and degradation phenotypes may go undetected in most preclinical safety assays designed to screen for acLQTS.
Gesehen am 09.05.2022